Australian women's experiences of receiving maternity care during the COVID-19 pandemic: A cross-sectional national survey - Wilson, A.N.; Sweet, L.; Vasilevski, V.; Hauck, Yvonne; Wynter, K.; Kuliukas, Lesley; Szabo, R.A.; Homer, C.S.E.; Bradfield, Zoe (WILEY, 2022)
Background: The COVID-19 pandemic has led to multiple changes in maternity services worldwide. Systems rapidly adapted to meet public health requirements aimed at preventing transmission of SARS-CoV-2, including quarantine procedures, travel restrictions, border closures, physical distancing and “stay-at-home” orders. Although these changes have impacted all stakeholders in maternity services, arguably the women at the center of this care have been most affected. This study aimed to explore women's experiences of receiving maternity care during the COVID-19 pandemic in Australia. Methods: A national cross-sectional online survey, including fixed choice and open-ended questions, was conducted during the first wave of the COVID-19 pandemic in Australia; pregnant and postnatal women were recruited through social media networks. Results: The survey was completed by 3364 women. Women felt distressed and alone due to rapid changes to their maternity care. Limited face-to-face contact with health practitioners and altered models of care often required women to accommodate significant changes and to coordinate their own care. Women felt that they were often “doing it alone,” due to public health restrictions on support people and visitors, both within and outside health services. Women described some benefits of visitor restrictions, such as, more time for rest, breastfeeding establishment, and bonding with their baby. Conclusions: This large nationwide Australian study provides unique data on women's experiences of receiving maternity care during the COVID-19 pandemic. Lessons learned provide an opportunity to rebuild and reshape the maternity sector to best meet the needs of women and their families during current and future public health crises.